Molecular Characteristics of Indonesian Isolate Enterocytozoon hepatopenaei Based on Sequence Analysis of 18S rRNA Genes - Slamet Budi Prayitno; Sarjito Sarjito; Desrina Desrina; Alfabetian Harjuna Condro Haditomo; Yohanes Kristiawan Artanto (Journal Omni-Akuatika, 2019)
ABSTRACT Enterocytozoon hepatopenaei (EHP) infection have been reported as an obstacle of whiteleg shrimp (Penaeus vannamei) culture in Indonesia. However, understanding of the molecular characteristics of EHP species in Indonesia is not widely known. The aims of this study were to determine the identity and characters of DNA, and their phylogeny of EHP species from several different locations in Indonesia with specific references to 18S rRNA gene. The EHPs were collected from cultured P.vannamei from Lampung, Pangandaran, Sidoarjo, Banyuwangi, Probolinggo, Blitar, Makassar, and Lombok. Thirteen (13) samples were randomly selected to explore their gene characters through 18S rRNA gene sequencing. The primers used were EHP_F and EHP_1R. Parameter observed were DNA sequencing, nucleotide sequence homology with related available genes in the Gen Bank database, multiple sequence alignment, and reconstruction of genetic relationship trees. DNA sequence homology analysis showed that all samples had 99.89-100% similarity to Indian Enterocytozoon hepatopenaei (Accession Number MH259890.1 and MH260592.1). The alignment results illustrated that all EHP sequences of Indonesian isolates were 100% identical each other. The phylogenetic tree topology provided information that all sample accessions were in the same clade and spread evenly. The conclusion were that the Indonesian EHP species were identical (100%) and it could be said that they were genetically homogeneous. Keywords: Enterocytozoon hepatopenaei, 18S rRNA gene, Indonesia.